2023
DOI: 10.1021/acsami.3c03461
|View full text |Cite
|
Sign up to set email alerts
|

Halloysite@Polyaniline Nanoparticles Loaded with the Praseodymium (III) Cation for Improving Active Corrosion Protection of Waterborne Epoxy Coating

Abstract: The corrosion resistance of the waterborne epoxy coating is poor during long-term service, which greatly limits its widespread application. In this paper, the halloysite nanotubes (HNTs) were modified by polyaniline (PANI) and then used as nanocontainers to encapsulate the green corrosion inhibitor praseodymium (III) cations (Pr 3+ ), obtaining HNTs@PANI@Pr 3+ nanoparticles. A scanning electron microscope, transmission electron microscopy, energy dispersive spectroscopy, Fourier transform infrared spectroscopy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…This electrochemical approach not only enhances surface adhesion but also allows for the inclusion of a corrosion-mitigating layer, making it a promising technique for achieving higher coating integrity and overall corrosion protection. , Polyaniline (PANI) and its derivatives are one of the most sought-after conductive polymers owing to their exceptional blend of high electrical conductivity, superior environmental stability, tunability, good processability, diverse synthesis methods, and cost-effectiveness . Recent studies have explored the incorporation of PANI into protective coatings to harness its unique properties for corrosion protection. , For instance, Tallman et al demonstrated the capacity of PANI to protect against corrosion through its catalytic capability of forming a passivating oxide layer . Although PANI manifests in various forms contingent on its oxidation level, emeraldine base (EB), its half-oxidized state, can undergo doping or protonation to yield the emeraldine salt (ES) form, recognized as the most conductive PANI state .…”
Section: Introductionmentioning
confidence: 99%
“…This electrochemical approach not only enhances surface adhesion but also allows for the inclusion of a corrosion-mitigating layer, making it a promising technique for achieving higher coating integrity and overall corrosion protection. , Polyaniline (PANI) and its derivatives are one of the most sought-after conductive polymers owing to their exceptional blend of high electrical conductivity, superior environmental stability, tunability, good processability, diverse synthesis methods, and cost-effectiveness . Recent studies have explored the incorporation of PANI into protective coatings to harness its unique properties for corrosion protection. , For instance, Tallman et al demonstrated the capacity of PANI to protect against corrosion through its catalytic capability of forming a passivating oxide layer . Although PANI manifests in various forms contingent on its oxidation level, emeraldine base (EB), its half-oxidized state, can undergo doping or protonation to yield the emeraldine salt (ES) form, recognized as the most conductive PANI state .…”
Section: Introductionmentioning
confidence: 99%
“…They are capable of absorbing inhibitors within their interior pores. Similar to GO, aniline undergoes in situ polymerization on hydroxides, carboxyl groups and within the interior pores of CNTs and HNTs (Tang et al, 2023;Najmi et al, 2021;Jalali et al, 2023).…”
Section: Methods To Prepare the Polyanilinementioning
confidence: 99%
“…Praseodymium (III) effectively modified PANI and achieved organic coatings with active protection performance. Tang et al (2023) concluded that the PANI waterborne epoxy coatings containing Pr 31 cationic corrosion inhibitor modified PANI, resulting in outstanding corrosion resistance with an i corr three orders of magnitude lower than that of the pure waterborne epoxy coatings. According to Samiee et al (2020), the coatings' highest corrosion protection resulted from the GO-PANIs modification with Pr 31 cations.…”
Section: Active Agentsmentioning
confidence: 99%